2018
DOI: 10.1080/21691401.2018.1443466
|View full text |Cite
|
Sign up to set email alerts
|

Generation of insulin-producing cells from human induced pluripotent stem cells on PLLA/PVA nanofiber scaffold

Abstract: Pancreatic tissue engineering as a therapeutic option for restoring and maintenance of damaged pancreas function has a special focus to using synthetic Scaffolds. This study was designed to evaluate pancreatic differentiation of human induced pluripotent stem cells (hiPSCs) on poly-L-lactic acid and polyvinyl alcohol (PLLA/PVA) scaffolds as 3 D matrix. During differentiation process, morphology of cells gradually changed and iPSCs derived insulin producing cells (iPSCs-IPCs) formed spherical shaped cell aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 33 publications
3
44
0
Order By: Relevance
“…Additionally, similar to Lahmy, in this work we demonstrated that endocrine marker of insulin was secreted from induced cells. Briefly, our findings were similar to Enderami [13], who showed that insulin secretion and C-peptide releasing in 3 D medium is higher than 2 D culture in 25 Mm glucose. As well as, our result is opposite to that of Enderami and Abazari (authors) who revealed that pancreatic marker Glut-2 has higher level in 3 D compared to 2 D it can be due to Figure 6.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Additionally, similar to Lahmy, in this work we demonstrated that endocrine marker of insulin was secreted from induced cells. Briefly, our findings were similar to Enderami [13], who showed that insulin secretion and C-peptide releasing in 3 D medium is higher than 2 D culture in 25 Mm glucose. As well as, our result is opposite to that of Enderami and Abazari (authors) who revealed that pancreatic marker Glut-2 has higher level in 3 D compared to 2 D it can be due to Figure 6.…”
Section: Discussionsupporting
confidence: 90%
“…In our study we: (1) made polymers that support long-term attachment, proliferation and differentiation of hiPSCs (2) successfully generated the insulin-producing cells from hiPSCs on hybrid scaffold. Similar to Enderami et al [13] our result showed that hiPSCs can tightly stick to scaffolds and penetrate to this hybrid. Also higher expression of pluripotent stem cell marker OCT-4 confirmed the intact characterization of these cells on hybrid scaffold in compared to gelatin coated cells was shown.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…33 Human iPSCs were cultured and expanded on a feeder layer of mitomycine-C (Sigma-Aldrich) inactivated mouse embryonic fibroblast (MEF) in iPSCs medium (Dulbecco's modified Eagle medium [DMEM]/F12 supplemented with 20% knockout serum replacement, 0.1 mmol/L nonessential amino acids, 2 mM l-glutamine, 0.1 mM β-mercaptoethanol, and 10 ng/mL of recombinant human basic fibroblast growth factor [bFGF], all from Invitrogen, Waltham, MA) in a 5% CO 2 and 95% humidity. 33 Human iPSCs were cultured and expanded on a feeder layer of mitomycine-C (Sigma-Aldrich) inactivated mouse embryonic fibroblast (MEF) in iPSCs medium (Dulbecco's modified Eagle medium [DMEM]/F12 supplemented with 20% knockout serum replacement, 0.1 mmol/L nonessential amino acids, 2 mM l-glutamine, 0.1 mM β-mercaptoethanol, and 10 ng/mL of recombinant human basic fibroblast growth factor [bFGF], all from Invitrogen, Waltham, MA) in a 5% CO 2 and 95% humidity.…”
Section: Expansion Of Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…Another approach is to use tissue engineering that comprising of three items, including scaffold, cells and growth factors. In this case, tissue engineered constructs could be the content of stem cells‐derived insulin producing cells (IPCs) that grew and differentiated on the polymeric scaffold (Enderami et al, ; Khorsandi, Nejad‐Dehbashi, Ahangarpour, & Hashemitabar, ; Mobarra, Soleimani, Pakzad, Enderami, & Pasalar, ). Among the polymers, those having higher biocompatibility and degradability are preferable.…”
Section: Introductionmentioning
confidence: 99%